ChemInform Abstract: Synthesis of γ, δ‐Unsaturated α‐Aminoaldehydes Using a Copper‐Catalyzed Vinylation Reaction Followed by a Claisen Rearrangement. Issue 44 (13th October 2016) - Ricard, Simon; Sanapo, Gabriel F.; Rahem, Neel; Daoust, Benoit
Abstract: A high‐yielding copper‐catalyzed coupling reaction of β‐iodoenamides with various allylic is described which is applicable to the transformation of alkyl or aryl alcohols, albeit generally low product yields are obtained.